Probabilistic analysis of the bearing capacity of inclined loaded strip footings near cohesive slopes. Issue 6 (3rd July 2021) - Brahmi, Narimane; Ouahab, Mohamed Younes; Mabrouki, Abdelhak; Benmeddour, Djamel; Mellas, Mekki
ABSTRACT: The bearing capacity of strip footings has been widely investigated using deterministic methods . In practise, soil properties are spatially variable, which makes the use of the probabilistic approach seem more reliable. In this article, a probabilistic study using finite element limit analysis, combined with random field theory, through OptumG2 code is carried out to evaluate the undrained bearing capacity of an inclined loaded strip footing adjacent to a slope. This article presents a new estimation of the probabilistic parameters effect on the mean bearing capacity factors μNc, and the mean failure envelopes, by taking into account the combination of load inclination and sloping ground. It is found that the coefficient of variation CovSu and the spatial correlation length Θ of soil shear strength have a significant effect on the undrained bearing capacity of the strip footing, in which the probabilistic analysis gives conservative values compared to the deterministic one.